Income and happiness: New results from generalized threshold and sequential models - Stefan Boes; Rainer Winkelmann (University of Zurich, Socioeconomic Institute, 2004)
Empirical studies on the relationship between income and happiness commonly use standard ordered response models, the most well-known representatives being the ordered logit and the ordered probit. However, these models restrict the marginal probability effects by design, and therefore limit the analysis of distributional aspects of a change in income, that is, the study of whether the income effect depend on a person's happiness. In this paper we pinpoint the shortcomings of standard models and propose two alternatives, namely generalized threshold and sequential models. With data of two waves of the German Socio-Economic Panel, 1984 and 1997, we show that the more general models yield different marginal probability effects than standard models.
Keywords: C25; I31; 330; ordered response models; marginal effects; subjective well-being; Einkommen; Lebensqualität; Lebensstandard; Schätzung; Deutschland